2017
DOI: 10.1017/s0033291717002045
|View full text |Cite
|
Sign up to set email alerts
|

A neurodevelopment and neuroplasticity-based framework for early intervention in psychotic disorders

Abstract: In recent years there has been growing interest in early intervention in psychotic disorders and a number of clinical and research programmes have been developed. The clinical staging model has been an essential part of early intervention as it provides the rationale of existing programmes. In medicine, clinical staging is a valuable approach in disorders where primary pathology is progressive in nature. However, the clinical staging model of psychosis has been proposed without establishing first that schizoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 67 publications
(129 reference statements)
0
3
0
Order By: Relevance
“…The current study has some limitations. The relevance of a staging model for schizophrenia has been questioned (Bora et al, 2017). Furthermore, investigating numbers of episodes as a marker of staging and clinical severity may be biased by disease characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…The current study has some limitations. The relevance of a staging model for schizophrenia has been questioned (Bora et al, 2017). Furthermore, investigating numbers of episodes as a marker of staging and clinical severity may be biased by disease characteristics.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the adult schizophrenia literature makes use of both neurodevelopmental and neuroplasticity theories and has emphasized early or preventative interventions for adolescents and adults (Bora, 2017). In fact, schizophrenia research over the past decades has demonstrated that early intervention positively affects adult neural connectivity and functional skill levels, resulting in more positive life outcomes (Buonocore et al, 2017; Lee et al, 2012; Ramsay and Macdonald, 2015).…”
Section: Lesson 1: Apply Prevention and Early Intervention Theoriesmentioning
confidence: 99%
“…In fact, interventions for the ill-defined transdiagnostic subclinical PSD in youth is not much different from interventions for a category of ‘youth with distress’. While there is no doubt that non-specific and general interventions for mild psychiatric presentations in youth (in any age group) might be helpful, accepting this approach as the ultimate goal would hamper the efforts to develop disorder-specific effective and true early intervention strategies for modifying the outcome of psychotic disorders (Bora, 2017).…”
mentioning
confidence: 99%